Філогенія та систематика роду Crataegus L. - Rubis, V.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The known phylogenetic systems of genus Crataegus L. has been analysis. The causes of difficult determine of species of this genus are elucidated. The characteristic of the important diagnostic signs of species of genus Crataegus has been done.